Network approaches for plant phylogenomic synteny analysis. (April 2017) - Zhao, Tao; Schranz, M Eric
Highlights: Network approaches can be used to investigate synteny between many species. We present a generalized approach for elucidating plant phylogenomic synteny. Synteny networks facilitate the interpretation of gene family evolution. An example network of B-class floral genes across angiosperms is presented. Abstract : Network analysis approaches have been widely applied across disciplines. In biology, network analysis is now frequently adopted to organize protein–protein interactions, organize pathways and/or to interpret gene co-expression patterns. However, comparative genomic analyses still largely rely on pairwise comparisons and linear visualizations between genomes. In this article, we discuss the challenges and prospects for establishing a generalized plant phylogenomic synteny network approach needed to interpret the wealth of new and emerging genomic data. We illustrate our approach with an example synteny network of B-class floral MADS-box genes. A broad synteny network approach holds great promise for understanding the evolutionary history of genes and genomes across broad phylogenetic groups and divergence times.